Influence of blood viscosity to cerebral blood flow in older humans compared to young subjects - Santos-Galduroz, Ruth F. [UNESP]; Bueno, Orlando F. A.; Yamaga, Lilian I.; Armani, Fernanda; Galduroz, Jose Carlos F. (Elsevier B.V., 2012)
Objective: Since blood viscosity (BV) is one of the most important factors determining blood flow, this study aimed to investigate the possible correlation between increased blood viscosity and reduction of regional cerebral blood flow (rCBF) in healthy ageing.Methods: Male subjects were distributed in two groups: "young", aged 20-30 (27 volunteers), or "elderly", aged 60-70 (50 volunteers). Whole blood viscosity was obtained with a Wells-Brookfield Cone/Plate Viscometer. Cerebral blood flow was analysed by means of single photon emission computed tomography (SPECT).Results: The mean BV values were 3.28 +/- 0.43 mPa in the group of young volunteers and 4.33 +/- 0.73 mPa in the group of elderly volunteers (t = -6.9, p < 0.0001). The elderly had a lower blood flow than the young in the following regions: bilateral parietal; temporal-parietal and temporal of the left hemisphere. Pearson's correlation between BV and rCBF showed a good inverse correlation when the BV was above 3.95 +/- 0.83 mPa.Conclusions: Our results point to a close relationship between the two parameters analysed, BV and rCBF. The impairment in rCBF observed in the elderly volunteers might be due to an increase in BV, among other factors.Significance: These findings suggest interesting possibilities for the treatment/prevention of brain ageing. (C) 2011 International Federation of Clinical Neurophysiology. Published by Elsevier B.V. All rights reserved.
Keywords: Cerebral blood flow; Blood viscosity; Ageing